Chronic Lymphocytic Leukemia Presenting as a Subcortical Watershed Infarct - Mridul Gupta; Divita Singh; Patrick Lee; Sandhya Kadiyam (Case Reports in Hematology)
Internal watershed infarcts (WI) involve white matter between deep and superficial arterial systems of middle cerebral artery. These infarcts are considered to be either from low blood flow or microembolism. Anemia is an extremely rare cause of watershed infarcts. Very few cases of hemolytic anemia causing watershed cerebral infarcts have been reported. Chronic lymphocytic leukemia (CLL) is frequently complicated with secondary autoimmune cytopenia such as autoimmune hemolytic anemia (AIHA), immune thrombocytopenia (ITP), and pure red cell aplasia. AIHA is present in about 7–10% of patients with CLL. AIHA from CLL presenting as WI is an extremely rare phenomenon with no previously published case reports to the best of our knowledge.